The Role of Job Insecurity, Compensation, and Job Satisfaction in Shaping Turnover Intention: Evidence from an Outsourcing Firm in Indonesia - Anggelika Ardila (Journal of Business Economics : Needs, Services, and Money, 2026)
This study examines the effects of job insecurity, compensation, and job satisfaction on turnover intention among employees in an outsourcing employment context in Indonesia. Drawing on psychological contract theory and prior turnover literature, this research aims to identify the relative importance of psychological and economic factors in explaining employees’ intention to leave. A quantitative approach was employed using survey data collected from 56 employees of a private outsourcing company. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that job insecurity has a positive and statistically significant effect on turnover intention, while compensation and job satisfaction do not show significant individual effects. However, the three variables jointly explain a substantial proportion of variance in turnover intention, indicating the multidimensional nature of employee turnover behavior. These findings suggest that perceived employment uncertainty plays a more dominant role than financial rewards or affective job evaluations in influencing turnover intention within contract-based employment settings. This study contributes to the turnover intention literature by highlighting the central role of job insecurity in outsourcing organizations and provides practical insights for managers seeking to reduce employee turnover through improved employment stability and communication strategies